Austria : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
The Austrian economy has been growing at an annual rate in excess of 3percent since mid-1999. Experience with deregulation in the telecommunications and electricity sectors is encouraged. With strong economic growth and expansionary monetary conditions from an Austrian perspective, Executive Directors judged that cyclical reasons would support a front-loaded approach to fiscal consolidation. Strong external demand and continued economic liberalization should contribute to sustaining economic expansion at a rate of close to 3percent per year in 2001-02.